Reverse innovation model: A proposal for the Colombian context (2019)
The reverse innovation is the generation of products and services with high impact on the market and low cost for companies in the future, many innovations in the emerging market, often by companies with resources and talent, From the public and with a very high creative potential; All these innovative products and services that can be used to be successful in a customer segment can be used as replicable models in high purchasing power markets. The importance of reverse innovation is not a purely academic issue, on the contrary, the intention of this document is to design a model in which companies can be a large reverse investment in companies and be world-class companies, based In a descriptive exploratory statement which seeks and we collect the different models of reverse innovation according to each author and from the construct to establish a model that considers the necessary elements adapted to the context of the emerging Colombian market. © 2019 Latin American and Caribbean Consortium of Engineering Institutions. All rights reserved.